2020
DOI: 10.1007/s13592-020-00764-3
|View full text |Cite
|
Sign up to set email alerts
|

Sterol addition during pollen collection by bees: another possible strategy to balance nutrient deficiencies?

Abstract: Sterols are essential nutrients for bees which are thought to obtain them exclusively from pollen. It is possible that variability in pollen sterol content shapes pollinator-flower relationships, as bee species require the physiological capacity or behavioral adaptations to cope with unfavorable sterolic composition of pollen. One behavioral adaptation used by generalist bees to avoid deficiencies is the mixing of different pollen types from multiple botanical families to achieve an optimal nutritional balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Bees are attracted to features of the pollen itself, such as the odor, outer lipid coat, or grain size, and to floral traits (Dobson 1988;Dobson and Bergström 2000;Lunau 2000;Lundin et al 2019;Pernal and Currie 2002;Rowe et al 2020). Much of pollen This is a U.S. government work and not under copyright protection in the U.S.; foreign copyright protection may apply, 2021 nutrition research to date focuses on protein and amino acids rather than lipids, which play key roles in energetic and physiological homeostasis (Brodschneider and Crailsheim 2010;Crailsheim 1990;de Groot 1953;Haydak 1970;Herbert et al 1977;Manning 2001Manning , 2008Manning et al 2007;Standifer 1967;Vanderplanck et al 2020). Lipids are emerging as a critical aspect of honey bee nutrition because of their positive effect on honey bee health (Annoscia et al 2017;Crone and Grozinger 2021;Stabler et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Bees are attracted to features of the pollen itself, such as the odor, outer lipid coat, or grain size, and to floral traits (Dobson 1988;Dobson and Bergström 2000;Lunau 2000;Lundin et al 2019;Pernal and Currie 2002;Rowe et al 2020). Much of pollen This is a U.S. government work and not under copyright protection in the U.S.; foreign copyright protection may apply, 2021 nutrition research to date focuses on protein and amino acids rather than lipids, which play key roles in energetic and physiological homeostasis (Brodschneider and Crailsheim 2010;Crailsheim 1990;de Groot 1953;Haydak 1970;Herbert et al 1977;Manning 2001Manning , 2008Manning et al 2007;Standifer 1967;Vanderplanck et al 2020). Lipids are emerging as a critical aspect of honey bee nutrition because of their positive effect on honey bee health (Annoscia et al 2017;Crone and Grozinger 2021;Stabler et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in analytical methods facilitate accurate quantitative chemical analysis of pollen, including fatty acids and protein-bound and free amino acids [97], sterols [98][99][100], plant secondary metabolites [101], and chemical elements [89]. The chemical/nutritional profile of the overall pollen diet of a bee individual can thus be calculated by integrating information on the proportional contributions of the nutritional profiles of pollen of all plant species visited for pollen collection (e.g., obtained through metabarcoding or palynological studies).…”
Section: Trends In Ecology and Evolutionmentioning
confidence: 99%
“…Differences in pollen nutritional content could therefore be largely determined by phylogenetic relatedness. For example, previous studies found a phylogenetic signal for pollen crude proteins and protein/lipid ratios [ 18 , 29 ], and for pollen sterols [ 19 , 33 ], but they have not considered amino acids contents and profiles.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of floral resources, most bees depend exclusively on pollen and nectar for nutrition at all stages of their life cycle [9,13,14], although some specialized bees use other resources such as floral oils, carrion, or resins [15]. Nectar provides the main source of carbohydrates [16,17] and pollen is the main source of proteins and lipids [16,[18][19][20][21][22]. As bees cannot synthesize amino acids de novo, pollen is crucial for larval growth and development as well as for adult growth, immune competence, longevity, and reproduction [19,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation